White spot syndrome virus and Enterocytozoon hepatopenaei in shrimp farms in Costa Rica: WSSV and EPH in white shrimp farms in Costa Rica - Peña Navarro, Nelson; Castro Vásquez, Ruth; Dolz, Gaby (Agronomía Mesoamericana, 2020)
Introduction. The white spot syndrome virus (WSSV) causes systemic destruction of ectodermal and mesodermal tissues in shrimp and can cause 100 % mortality. Enterocytozoon hepatopenaei (EHP) is an intracellular microsporidian that causes lysis of epithelial cells in hepatopancreatic tubules in shrimp. Objective. Detect the presence of WSSV and EHP in fifteen shrimp farms in the Gulf of Nicoya and the Central Pacific from Costa Rica. Materials and methods. Between January 2017 and July 2018 water during the filling process of the pond, postlarvae, and juvenile shrimp of Penaeus vannamei was collected, during a production cycle in each one of the fifteen farms. Samples were analyzed through polymerase chain reaction (PCR) using primers and protocols to detect the VP41B gene in WSSV, and the small subunit ribosomal RNA gene of EHP. Results. The presence of WSSV was detected in one farm, while EHP was not detected in any of the fifteen farms. The sequencing of the amplified segments of the VP41B gene showed 100 % identity with isolated shrimp sequences in Taiwan and Mexico. Conclusion. WSSV was detected at a very low frequency and EHP was not detected in this study. It is necessary to continue monitoring these agents in the country’s shrimp farms.